Performance Characteristic Of Single Stage Micro Gas Turbine (MGT) Running On Liquid Biofuels - Poo, Chee Shen (Universiti Sains Malaysia, 2018)
Biofuels are the future interest on renewable green fuels, especially in rural areas which the difficulties in diesel transportation for the running of the diesel generator set. Nevertheless, there are plenty of biomass which can be make use of, to replace diesel in rural areas. The liquid biofuel micro gas turbine can solve the problem of the diesel high price issue and combined heat power problem in diesel generator set. A micro gas turbine is an energy generator which is developed from gas turbine combustion system. In addition, micro gas turbine running on liquid biofuels is getting attraction globally due to the environmentally friendly and the ability to recirculate the wasted biomass. The performance of the micro gas turbine running with biofuels have to be evaluate and study to further develop the system. In this project, the performance of the micro gas turbine is characterised with diesel combustion which acts as the benchmark to the system. The biofuels used in the project is the blending of diesel and vegetable oil in certain ratio, for example, B10 means 10 percent of vegetable oil and 90 percent of diesel. The most optimum blending ratio is found out and compare with the diesel. The main focus is on the power output, specific fuel consumption and emission of carbon monoxide (CO) and nitrogen oxide (NOx). In this project, the highest turbine power is 10.365 kW for micro gas turbine running on diesel and the lowest specific fuel consumption for micro gas turbine running on diesel is 0.1215 kg/kWh. The result indicate that the biofuel can produce almost similar turbine power as the diesel, however, with the sacrifice of the specific fuel consumption performance. Furthermore, the biofuels have much higher CO emission and NOx emission compare to diesel, in the meanwhile, the CO emission decrease with higher temperature and higher equivalence ratio, contrarily, NOx emission increase with higher temperature and higher equivalence ratio. The most optimum biofuel is B80 which has a lower CO emission and NOx emission at higher temperature.